Fecundity of Sebastes mentella and Sebastes norvegicus in the Irminger Sea and Icelandic waters - Fran Saborido-Rey; Rosario Domínguez-Petit; Dolores Garabana; Þhorstein Sigurðsson (Ciencias Marinas, 2015)
Fecundity of redfish Sebastes mentella and Sebastes norvegicus in the Irminger Sea and Icelandic waters was analyzed in relation to several maternal features and oocyte developmental stages. The mean potential fecundity in S. norvegicus was estimated to be 123,300 oocytes and relative fecundity averaged 116 oocytes g–1. Mean potential fecundity in S. mentella was 50,013 oocytes and relative fecundity was 64 oocytes g–1. Strong fecundity down-regulation (50% on average) was observed during oocyte development estimated from September to November, when oocytes reached the advanced stage of vitellogenesis. This result implies that fecundity can only be comparable between individuals presenting the same stage of oocyte development. However, the development rates differed between species and between stocks, and therefore the same stage is reached at a different time of the year. Fecundity varied significantly with female weight and length, while condition had little influence on fecundity variation.